Kecerdasan emosi lelaki dalam novel-novel terpilih Anwar Ridhwan dan Haruki Murakami: Kajian perbandingan / Maznida Mahadi - Maznida , Mahadi (2019)
This study conducted to identify and compare the aspects of emotional intelligence between Malay and Japanese men. Emotional intelligence equations and differences are analysed based on the emotional forms and aspects of emotional intelligence emphasized by Daniel Goleman (1995/1999) in the Goleman's Emotional Intelligence Theory. The objective of this study are to identify the emotional forms, to analysis the emotional intelligence and to compare the similarities and differences in emotional intelligence that were found in the characters in the novels of Hari-Hari Terakhir Seorang Seniman (1979/2009) and Penyeberang Sempadan (2012) by Anwar Ridhwan, Kafka on the Shore (2005) and Colorless Tsukuru Tazaki and His Years of Pilgrimage (2014) by Haruki Murakami. The presence of the most powerful and dominant emotions in Malay and Japanese male characters are detected through the analysis table and shown through the pie chart to compare the emotional which are most emphasized by Anwar Ridhwan and Haruki Murakami in all four study novels. The comparison of the emotional intelligence elements in male characters based on two components of Emotional Intelligence introduced by Daniel Goleman. That is personal competence and social efficiency, which divided to five aspects, Self-awareness, Self-regulation, Motivation, Empathy and Social Skills. The findings show that all the novels studied are relevant to the Goleman's Emotional Intelligence Theory and meet the objectives of the study. The Malay and Japanese male characters showed the balance of emotional forms and emotional intelligence. There are no negative emotions detected. The results of these analysis show that Malay and Japanese men show the same strong emotion. There is no major difference between the emotion of Malay and Japanese men characters. The results of this study clearly demonstrate that emotional forms and emotional intelligence aspects exhibited by Malay and Japanese men characters are equivalent.